Crohn's disease initiated with extraintestinal features. Issue 4 (20th April 2019) - Chang, Jeffrey; Li, Chia-Cheng; Achtari, Marina; Stoufi, Eleana
Abstract : Crohn's disease (CD) is a multifactorial, chronic immune-mediated disorder. The oral cavity is involved in 0.5% to 20% of the patients with CD. Oral manifestations of CD are sometimes nonspecific and can be overlooked by the clinicians. These manifestations may precede intestinal symptoms and can serve as indicators for early diagnosis. To increase awareness and to contribute to the standard intervention, here we report a paediatric case with persistent idiopathic swelling of the lower lip and perianal fistula. Microscopic examinations revealed multiple non-necrotising granulomas with chronic inflammation, oedema and lymphangiectasia. The patient was treated with metronidazole 500 mg and ciprofloxacin 500 mg twice a day for one month. The perioral lesions were managed with topical 0.03% tacrolimus and oral prednisone 10 mgtwice a day for one month, followed by a tapered regimen of 10 mg/day for another month. The patient's symptoms improved without full remission at the 6-month follow-up.